A leaders's guide to after-action reviews - and U.S. Army (Department of the Army, 1993)
An after-action review (AAR) is a professional discussion of an event, focused on performance standards, that enables soldiers to discover for themselves what happened, why it happened, and how to sustain strengths and improve on weaknesses. It is a tool leaders and units can use to get maximum benefit from every mission or task. It provides- Candid insights into specific soldier, leader, and unit strengths and weaknesses from various perspectives. Feedback and insight critical to battle-focused training. Details often lacking in evaluation reports alone. Evaluation is the basis for the commander's unit-training assessment. No commander, no matter how skilled, will see as much as the individual soldiers and leaders who actually conduct the training. Leaders can better correct deficiencies and sustain strengths by carefully evaluating and comparing soldier, leader, and unit performance against the standard. The AAR is the keystone of the evaluation process. Feedback compares the actual output of a process with the intended outcome. By focusing on the task's standards and by describing specific observations, leaders and soldiers identify strengths and weaknesses and together decide how to improve their performances. This shared learning improves task proficiency and promotes unit bonding and esprit. Squad and platoon leaders will use the information to develop input for unittraining plans. The AAR is a valid and valuable technique regardless of branch, echelon, or training task. Of course, AARs are not cure-alls for unit-training problems. Leaders must still make on-the-spot corrections and take responsibility for training their soldiers and units. However, AARs are a key part of the training process. The goal is to improve soldier, leader, and unit performance. The result is a more cohesive and proficient fighting force. Because soldiers and leaders participating in an AAR actively discover what happened and why, they learn and remember more than they would from a critique alone. A critique only gives one viewpoint and frequently provides little opportunity for discussion of events by participants. Soldier observations and comments may not be encouraged. The climate of the critique, focusing only on what is wrong, prevents candid discussion of training events and stifles learning and team building.